2009
DOI: 10.1111/j.1471-4159.2009.06075.x
|View full text |Cite
|
Sign up to set email alerts
|

α‐Synuclein induces migration of BV‐2 microglial cells by up‐regulation of CD44 and MT1‐MMP

Abstract: Although there is known to be a marked concentration of reactive microglia in the substantia nigra pars compacta (SNpc) of patients with Parkinson’s disease (PD), a disorder in which α‐synuclein plays a key pathogenic role, the specific roles of α‐synuclein and microglia remains poorly understood. In this study, we investigated the effects of α‐synuclein and the mechanisms of invasive microglial migration into the SNpc. We show that α‐synuclein up‐regulates the expressions of the cell adhesion molecule CD44 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 66 publications
2
46
0
1
Order By: Relevance
“…The soluble CD44 can liberate microglia from the surrounding extracellular matrix for migration. The identical effects were also displayed in the murine microglia BV-2 cells [44].…”
Section: Neuroinflammationsupporting
confidence: 60%
“…The soluble CD44 can liberate microglia from the surrounding extracellular matrix for migration. The identical effects were also displayed in the murine microglia BV-2 cells [44].…”
Section: Neuroinflammationsupporting
confidence: 60%
“…Previously, it has been demonstrated that the p38 and ERK1/ ERK2 (p44/42) families of MAPK pathways play a prominent role in activation of the microglial cell in chronic neurodegenerative diseases such as AD (55-58) and Parkinson's disease (59,60). Both p38 and ERK1/ERK2 MAPK activation has been shown to be essential for IL-1, IL-6, and TNF-a expression and NO release (61).…”
Section: Human Truncated T Stimulates Activation Of Microglia Throughmentioning
confidence: 99%
“…For example, several studies have demonstrated that extracellular and nigral Syn-containing aggregates are often surrounded by activated microglia or inflammatory mediators in PD brains (McGeer et al, 1988;Yamada et al, 1992), similarly to what has been described for amyloid plaques in AD (Griffin et al, 2006). Moreover, the extent of microglial activation in the SN from PD patients has been found to be correlated with the degree of Syn accumulation (Croisier et al, 2005) and with increased Syn levels as evidenced by in vitro (Kim et al, 2009;Klegeris et al, 2008) and in vivo (Lee et al, 2009a) studies, strongly supporting the view that the protein has a major role in phenotypic changes of microglia. Up to this point, a considerable number of in vivo studies with animal models of PD that directly link Syn with microglial activation have been reported.…”
Section: Syn-induced Microglial Activationmentioning
confidence: 51%